Load Carrying Capacity of Drift Pin Joint of Cross Laminated Timber (CLT) with Steel Insert Plate - Shoichi Nakashima; Akihisa Kitamori; Kohei Komatsu (Masyarakat Peneliti Kayu Indonesia, 2012)
Cross Laminated Timber (CLT) is a structural plate element which is approved in Europe and is intended to be approved in Japan. It consists of small dimension laminae, in which laminae parallel and perpendicular to longitudinal direction are interlaminated. We performed tensile tests for the drift pin joint with steel insert plate. Specimen consisted of CLT was made from Japanese cedar laminae (thickness of laminae t = 30mm, five laminae were layered), with steel drift pin plate. Odd-numbered layers were parallel to the longitudinal axis, and even-numbered layers were perpendicular to the longitudinal axis. The experimental parameters were edge distances (3d, 4d and 7d), end distances (3d, 4d and 7d) and diameters of pin (12 and 16 mm) and the replication were three respectively. Initial stiffness was lower than the results of glulam drift pin joint loaded in parallel to the grain, however second stiffness after the yield of drift pin was higher because the lateral compression occurred at even-numbered layers. Additionally, ductility was higher because split failures around the pin were prevented by the glued effect of interlaminated layers. As the characteristic value of test results, initial stiffness K, yield load Py, maximum load Pmax, indicated the effect of the difference of the diameter of the pin, while deformation capacity indicated the effect of edge distance.